Available and novel plant-based carbon dots derived from Vaccaria Semen carbonisata alleviates liver fibrosis - Zhao, Yafang; Dai, Ertong; Dong, Liyang; Yuan, Jinye; Zhao, Yusheng; Wu, Tong; Kong, Ruolan; Li, Menghan; Wang, Shuxian; Zhou, Long; Yang, Yingxin; Kong, Hui; et al. (Frontiers in Molecular Biosciences, 2023)
Background: Liver fibrosis represents an intermediate stage in the progression of liver disease, and as of now, there exists no established clinical therapy for effective antifibrotic treatment. Purpose: To explore the impact of Carbon dots derived from Vaccaria Semen Carbonisata (VSC-CDs) on carbon tetrachloride-induced liver fibrosis in mice. . methods: VSC-CDs were synthesized employing a modified pyrolysis process. Comprehensive characterization was performed utilizing various techniques, including transmission electron microscopy (TEM), multiple spectroscopies, X-ray photoelectron spectroscopy (XPS), and high-performance liquid chromatography (HPLC). A hepatic fibrosis model induced by carbon tetrachloride was utilized to evaluate the anti-hepatic fibrosis effects of VSC-CDs.Results: VSC-CDs, exhibiting a quantum yield (QY) of approximately 2.08%, were nearly spherical with diameters ranging from 1.0 to 5.5 nm. The VSC-CDs prepared in this study featured a negative charge and abundant chemical functional groups. Furthermore, these particles demonstrated outstanding dispersibility in the aqueous phase and high biocompatibility. Moreover, VSC-CDs not only enhanced liver function and alleviated liver damage in pathomorphology but also mitigated the extent of liver fibrosis. Additionally, this study marks the inaugural demonstration of the pronounced activity of VSC-CDs in inhibiting inflammatory reactions, reducing oxidative damage, and modulating the TGF-β/Smad signaling pathway. Conclusion:VSC-CDs exerted significant potential for application in nanodrugs aimed at treating liver fibrosis.